The use of social media in ethic digital perspective - Rawanoko, Endrise Septina; Komalasari, Kokom; Al-Muchtar, Suwarma; Bestari, Prayoga (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
Penggunaan media sosial pada mahasiswa menjadi salah satu gaya hidup di lingkungan Universitas Wisnuwardhana Malang. Pada era digital seperti saat ini penggunaan media sosial sering disalah gunakan bahkan menjadi ajang bully, rasis, dsb. Untuk itu penggunaan media sosial perspektif digital ethic hadir sebagai cara untuk meminimalisir kebobrokan moral anak didik di media sosial. Riset ini berfokus pada penggunaan media sosial perspektif digital ethic pada mahasiswa di Universitas Wisnuwardhana Malang. Metode penelitian ini adalah kualitatif deskriptif. Hasil dari penelitian di lapangan mengenai penggunaan media sosial dan perspektif digital ethic adalah mayoritas mahasiswa Universitas Wisnuwardhana Malang menggunakan media hanya untuk memposting foto-foto pribadi serta kegiatan yang positif. Sistem komunikasi sosial yang ada di media sosial, sama persis dengan sistem komunikasi dalam lingkungan sehari-hari. Mahasiswa Universitas Wisnuwardhana Malang mempertimbangkan dalam mengupload ataupun memposting di media sosial. ABSTRACTThe use of social media for students is one of the lifestyles in the University of Wisnuwardhana Malang. In this digital era, the use of social media is often misused. It even becomes an arena for bullying, racism, etc. For this reason, the use of social media with an ethical digital perspective is present to minimize the moral decay of students on social media. This research focuses on using social media with a digital ethics perspective on students at Wisnuwardhana University Malang. This research method is descriptive qualitative. The research results in the field regarding the use of social media and the digital ethics perspective are that many Wisnuwardhana University Malang students use the media only to post personal photos and positive activities. The social communication system in social media is precisely the same as the communication system in everyday life. Wisnuwardhana University Malang students consider uploading or posting on social media